Being and performing the masculinity in Karim Raslan's Go East - Collin, Jerome (Institute Of Research And Community Outreach - Petra Christian University, 2008)
This paper explores the concept of being and performing masculinity in Karim Raslan’s short story Go East. Torn between being a man in his own terms and performing socially endorsed masculine roles and sexual desires, the protagonist, Mahmud, negotiates and transgresses gender borders, resulting in his inability to sexually perform with women and incapacity for emotional and physical intimacy with men. Yet, he overcomes his impotence through heterosexual intercourse despite imagining making love to men.